Family Size Effects on Child Health: Evidence on the Quantity-Quality Trade-off using the NLSY - Kabir Dasgupta; Keisha T.-Solomon (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2017)
In this study, we use matched mother-child data from the National Longitudinal Surveys to study family size effects on child health. Focussing on body weight indicators as our health outcome of interest, we examine the effects of exogenous variations in family size on child health. We find no significant empirical support in favor of the quantity-quality trade-off theory. To combat potential empirical concerns associated with cross-sectional analysis, we make use of the panel aspects of the data and employ child fixed effects. Findings from our panel data analysis suggest that birth of a younger sibling is related to a decline in the likelihood of being overweight. Furthermore, birth of younger siblings at higher parities leads to a significant drop in the likelihood of obesity (but may also lead to an increase in the child's probability of being underweight).
Keywords: J13; I10; 330; Family Size; Children; Underweight; Overweight; Obesity; Health; Instrumental Variables; Fixed Effects